Oxygen vacancy-enriched WO3-W18O49 composite catalytic material as well as preparation method and application thereof
Through the oxygen-rich vacancies WO3-W18O49 composite catalytic material, the problem of WO3 photocatalyst is solved inefficient in cyclohexanyl oxidation reaction, broadening the light absorption band and providing additional active sites, improving the performance and stability of the catalyst. A more efficient catalytic reaction is achieved.
Patent Information
- Application Number
- CN202411410564.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
As a photocatalyst, WO3 has problems such as insufficient light absorption range and high photogenerating holes and electron recombination rates in the cyclohexanyl oxidation reaction, which leads to low efficiency in the catalytic reaction.
Using oxygen-rich vacancies WO3-W18O49 composite catalytic material, the light absorption band is broadened by changing the surface and electronic structure of the catalyst, and additional active sites are provided through the oxygen vacancies to improve the adsorption and reaction capacity of the catalyst.
The light absorption capacity and catalytic activity of the catalyst are improved, the efficiency of cyclohexanyl oxidation reaction is improved, and good performance is maintained during long-term reactions, reducing the degradation rate of the catalyst.
Smart Images

Figure CN119281318A_ABST
Abstract
Description
Technical Field
[0001] The present invention discloses a composite catalytic material; specifically, a composite catalytic material having oxygen vacancies WO3-W 18 O 49 The invention discloses a composite catalytic material and a preparation method and application of the catalyst, belonging to the technical field of catalysts. Background Art
[0002] The selective oxidation of cyclohexane to cyclohexanone and cyclohexanol (KA oil for short) is a great challenge in the field of catalytic engineering and modern chemical processes. The inherent chemical stability of the CH bonds in cyclohexane requires harsh reaction conditions, which usually involve temperatures of 150-170 °C and pressures of about 10-20 standard atmospheres in an industrial environment. These conditions often lead to the formation of unwanted by-products, which reduce the overall process selectivity and increase operating costs. Therefore, achieving high selectivity while maintaining optimal conversion remains a primary goal in the field of cyclohexane catalytic oxidation research.
[0003] Semiconductor catalytic technology can solve the technical bottleneck of this reaction. WO3 is a traditional photocatalytic material, but its light absorption range is lower than 450nm, and its light utilization rate is extremely low. In addition, due to the high recombination rate of photogenerated holes and electrons formed during the oxidation process of WO3, it is difficult to use in catalytic reactions. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of WO3 in participating in the reaction as a photocatalyst, to reduce the recombination rate of photogenerated holes and electrons when WO3 participates in the reaction, to improve the light absorption band of WO3 and the conversion rate of WO3 in the cyclohexane oxidation reaction, and to provide an oxygen-rich vacancy WO3-W 18 O 49 In composite catalytic materials, oxygen vacancies play a key role in changing the adsorption capacity of catalysts to alkanes by changing the surface and electronic structure, thereby affecting the oxidation process. 18 O 49 It also absorbs in the visible light band. WO3-W 18 O 49 The absorption band of the composite material is broadened to the visible light band.
[0005] The first object of the present invention is to provide an oxygen-rich vacancy WO3-W 18 O 49 A method for preparing a composite catalytic material.
[0006] The second object of the present invention is to provide the oxygen-rich vacancy WO3-W prepared by the above preparation method. 18 O 49 Composite photothermal catalytic materials.
[0007] The third object of the present invention is to improve the oxygen-rich vacancy WO3-W 18 O 49 Application of composite catalytic materials.
[0008] To this end, the first technical solution provided by the present invention is as follows:
[0009] A kind of oxygen vacancy-rich WO3-W 18 O 49 The preparation method of the composite catalytic material comprises the following steps in sequence:
[0010] S1. Preparation of WO3 nanorods:
[0011] Add tungsten source and sodium chloride to ultrapure water, and use hydrochloric acid to adjust the pH of the solution to acidic, and perform hydrothermal reaction at 180°C for 20-24h. The reaction product is eluted and dried to obtain WO3 nanorods;
[0012] The molar ratio of sodium tungstate dihydrate to sodium chloride is 1:1.5-1:2;
[0013] S2. Preparation of WO3-W 18 O 49
[0014] Tungsten hexachloride was added to anhydrous ethanol, and then the solution was transferred to WO3 nanorods and dispersed evenly by ultrasonication, and then a hydrothermal reaction was carried out at 160°C for 24 hours.
[0015] The reaction product is eluted and dried to obtain WO3-W 18 O 49 :
[0016] The molar ratio of tungsten hexachloride to WO3 nanorods is 1:3-1:30;
[0017] Furthermore, the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite catalytic material, the tungsten source described in S1 is sodium tungstate dihydrate.
[0018] Furthermore, the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite catalytic material, the pH described in S1 is 2.
[0019] Furthermore, the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite catalytic material, the tungsten source described in S2 is tungsten hexachloride.
[0020] Furthermore, the above-mentioned oxygen-rich vacancy WO3-W18 O 49 In the preparation method of the composite catalytic material, the washing in step 1) is first performed with water and then with anhydrous ethanol.
[0021] Furthermore, the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 In the preparation method of the composite catalytic material, the washing in step 2) is first performed with water and then with anhydrous ethanol.
[0022] The second technical solution provided by the present invention is the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 The composite catalytic material is prepared by the method provided by the first technical solution.
[0023] The last technical solution of the present invention is to provide the above-mentioned oxygen-rich vacancy WO3-W 18 O 49 The composite catalytic material is used for photothermal catalytic cyclohexane oxidation reaction.
[0024] The present invention provides a method for photothermal catalytic cyclohexane oxidation reaction, which comprises the following steps in sequence:
[0025] 1) Weigh WO3-W 18 O 49 -150 composite photothermal catalytic material is dissolved in cyclohexane and acetone;
[0026] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.0-2.0 MPa;
[0027] 3) React at 100-150°C under xenon lamp irradiation for 6-10 hours;
[0028] 4) After the reaction is completed, wait for the reactor to cool to room temperature and measure the conversion rate and selectivity;
[0029] The WO3-W 18 O 49 The ratio of -150 composite photothermal catalytic material to cyclohexane is 20 mg:10 mL.
[0030] The volume ratio of cyclohexane to acetone is 2:1
[0031] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0032] 1. The technical solution provided by the present invention utilizes oxygen vacancies to change the electronic structure of the catalytic material, increase the light absorption capacity of the material, and improve the photocatalytic activity, thereby improving the efficiency of catalytic cyclohexane oxidation. 18 O 49The oxygen vacancies in the composite catalytic material can provide additional active sites for the reaction, serving as adsorption and reaction centers, thereby improving the performance of the catalyst during the reaction.
[0033] 2. The technical solution provided by the present invention optimizes the durability of the catalyst material by introducing oxygen vacancies, making WO3-W 18 O 49 The composite catalytic material maintains good performance during long-term reactions and reduces the degradation rate of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 WO3, W 18 O 49 and WO3-W 18 O 49 TEM image of composite photothermal catalytic material;
[0035] Figure 2 WO3, W 18 O 49 and WO3-W 18 O 49 HRTEM and EDS images of composite photothermal catalytic materials;
[0036] Figure 3 WO3, W 18 O 49 and WO3-W 18 O 49 Infrared absorption spectrum of composite photothermal catalytic material;
[0037] Figure 4 WO3, W 18 O 49 and WO3-W 18 O 49 XRD pattern of composite photothermal catalytic material;
[0038] Figure 5 WO3, W 18 O 49 and WO3-W 18 O 49 UV-visible absorption spectrum and Tauc plot of composite photothermal catalytic materials;
[0039] Figure 6 WO3, W 18 O 49 and WO3-W 18 O 49 Performance comparison of composite photothermal catalytic materials for photothermal cyclohexane oxidation; DETAILED DESCRIPTION
[0040] The claims of the present invention are further described in detail below in conjunction with specific embodiments, but do not constitute any limitation to the present invention. Any limited modifications made by anyone within the scope of the claims of the present invention are still within the scope of the claims of the present invention.
[0041] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.
[0042] Example 1
[0043] This embodiment provides an oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite photothermal catalytic material comprises the following steps:
[0044] 1) Synthesis of WO3 nanorods
[0045] 2.5mmol of sodium tungstate dihydrate and 5mmol of sodium chloride were added to 19mL of ultrapure water and ultrasonically dispersed to a transparent solution. Then, an appropriate amount of 3M HCl was added dropwise to adjust the pH of the solution to 2, and the solution was reacted at 180℃ in a polytetrafluoroethylene reactor for 20 hours. After cooling to room temperature, the solution was washed once with water, then washed several times with anhydrous ethanol, and dried to obtain WO3 nanorods.
[0046] 2) WO3-W 18 O 49 -30 Synthesis
[0047] 0.076 mmol of tungsten hexachloride was added to 30 ml of anhydrous ethanol to dissolve, and then the solution was transferred to the WO3 nanorods in step 1) and ultrasonically dispersed evenly. The reaction was carried out in a polytetrafluoroethylene reactor at 160°C for 24 hours, and after cooling to room temperature, it was washed with deionized water and anhydrous ethanol for 2-3 times and dried to obtain WO3-W 18 O 49 -30 composite photothermal catalytic material.
[0048] Example 2
[0049] This embodiment provides an oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite photothermal catalytic material comprises the following steps:
[0050] 1) Synthesis of WO3 nanorods
[0051] 2.5mmol of sodium tungstate dihydrate and 5mmol of sodium chloride were added to 19mL of ultrapure water and ultrasonically dispersed to a transparent solution. Then, an appropriate amount of 3M HCl was added dropwise to adjust the pH of the solution to 2, and the solution was reacted at 180℃ in a polytetrafluoroethylene reactor for 20 hours. After cooling to room temperature, the solution was washed once with water, then washed several times with anhydrous ethanol, and dried to obtain WO3 nanorods.
[0052] 2) WO3-W 18 O 49 -150 Synthesis
[0053] 0.38 mmol of tungsten hexachloride was dissolved in 30 ml of anhydrous ethanol, and then the solution was transferred to the WO3 nanorods in step 1) and dispersed evenly by ultrasonication. The reaction was carried out in a polytetrafluoroethylene reactor at 160°C for 24 hours, and after cooling to room temperature, the reaction was washed with deionized water and anhydrous ethanol for 2-3 times, and dried to obtain WO3-W 18 O 49 -150 composite photothermal catalytic material.
[0054] Example 3
[0055] This embodiment provides an oxygen-rich vacancy WO3-W 18 O 49 The preparation method of the composite photothermal catalytic material comprises the following steps:
[0056] 1) Synthesis of WO3 nanorods
[0057] 2.5mmol of sodium tungstate dihydrate and 5mmol of sodium chloride were added to 19mL of ultrapure water and ultrasonically dispersed to a transparent solution. Then, an appropriate amount of 3M HCl was added dropwise to adjust the pH of the solution to 2, and the solution was reacted at 180℃ in a polytetrafluoroethylene reactor for 20 hours. After cooling to room temperature, the solution was washed once with water, then washed several times with anhydrous ethanol, and dried to obtain WO3 nanorods.
[0058] 2) WO3-W 18 O 49 -300 Synthesis
[0059] 0.76 mmol of tungsten hexachloride was dissolved in 30 ml of anhydrous ethanol, and then the solution was transferred to the WO3 nanorods in step 1) and dispersed evenly by ultrasonication. The reaction was carried out in a polytetrafluoroethylene reactor at 160°C for 24 hours, and after cooling to room temperature, the reaction was washed with deionized water and anhydrous ethanol for 2-3 times, and dried to obtain WO3-W 18 O 49 -300 composite photothermal catalytic material.
[0060] Application Example 1
[0061] This application example uses the WO3-W provided in Example 1. 18 O 49 -30 composite photothermal catalytic material catalyzes the photothermal catalytic reaction of cyclohexane, and the reaction process specifically includes the following steps:
[0062] 1) Weigh 20 mg of WO3-W 18 O 49 -30 composite photothermal catalytic material was dissolved in 10 mL cyclohexane and 5 mL acetone;
[0063] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.5 MPa;
[0064] 3) React at 120°C under xenon lamp irradiation for 8 hours;
[0065] 4) After the reaction was completed, the reactor was cooled to room temperature, and the solution after the reaction was taken out and measured by gas chromatography. The conversion rate was 7.12% and the selectivity was 98.79%.
[0066] Application Example 2
[0067] This application example uses the WO3-W provided in Example 2 18 O 49 -150 composite photothermal catalytic material catalyzes the photothermal catalytic reaction of cyclohexane, and the reaction process specifically includes the following steps:
[0068] 1) Weigh 20 mg of WO3-W 18 O 49 -150 composite photothermal catalytic material was dissolved in 10 mL cyclohexane and 5 mL acetone;
[0069] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.5 MPa;
[0070] 3) React at 120°C under xenon lamp irradiation for 8 hours;
[0071] 4) After the reaction was completed, the reactor was cooled to room temperature, and the solution after the reaction was taken out and the conversion rate was 8.46% and the selectivity was 99.01% by gas chromatography.
[0072] Application Example 3
[0073] This application example uses the WO3-W provided in Example 3 18 O 49 -300 composite photothermal catalytic material catalyzes the photothermal catalytic reaction of cyclohexane, and the reaction process specifically includes the following steps:
[0074] 1) Weigh 20 mg of WO3-W 18 O 49-300 composite photothermal catalytic material was dissolved in 10 mL cyclohexane and 5 mL acetone;
[0075] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.5 MPa;
[0076] 3) React at 120°C under xenon lamp irradiation for 8 hours;
[0077] 4) After the reaction was completed, the reactor was cooled to room temperature, and the solution after the reaction was taken out and measured by gas chromatography. The conversion rate was 7.52% and the selectivity was 98.99%.
[0078] Comparative application example 1
[0079] In this comparative application example, WO3 catalyzes the photothermal catalytic reaction of cyclohexane, and the reaction process specifically includes the following steps:
[0080] 1) Weigh 20 mg of WO3 and dissolve it in 10 mL of cyclohexane and 5 mL of acetone;
[0081] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.5 MPa;
[0082] 3) React at 120°C under xenon lamp irradiation for 8 hours;
[0083] 4) After the reaction was completed, the reactor was cooled to room temperature, and the solution after the reaction was taken out and measured by gas chromatography. The conversion rate was 4.92% and the selectivity was 97.78%.
[0084] Comparative Application Example 2
[0085] This comparative application example W 18 O 49 The photothermal catalytic reaction of cyclohexane is catalyzed, and the reaction process specifically includes the following steps:
[0086] 1) Weigh 20 mg of W 18 O 49 Dissolve in 10 mL cyclohexane and 5 mL acetone
[0087] 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.5 MPa;
[0088] 3) React at 120°C under xenon lamp irradiation for 8 hours;
[0089] 4) After the reaction was completed, the reactor was cooled to room temperature, and the solution after the reaction was taken out and the conversion rate was 6.52% and the selectivity was 98.52% by gas chromatography.
[0090] Through the above application examples and comparative application examples, it can be seen that WO3 nanorods, W18 O 49 WO3-W 18 O 49 -30, WO3-W 18 O 49 -150, WO3-W 18 O 49 -300 under the same conditions, its WO3-W 18 O 49 The conversion rate of cyclohexane oxidation by photothermal catalysis of W-30 is 1.45 times that of pure WO3. 18 O 49 1.09 times of WO3-W 18 O 49 The conversion rate of cyclohexane oxidation by photothermal catalysis at -150° is 1.72 times that of pure WO3. 18 O 49 1.30 times of WO3-W 18 O 49 The conversion rate of cyclohexane oxidation by photothermal catalysis of W-300 is 1.53 times that of pure WO3. 18 O 49 1.15 times of WO3-W 18 O 49 The catalytic performance of the composite material in the photothermal catalytic cyclohexane oxidation reaction is stronger than that of pure WO3 and pure W 18 O 49 , which improves the photothermal catalytic performance of the material.
[0091] In order to better understand the present application, the experimental results of the embodiments are further analyzed and explained in conjunction with the accompanying drawings.
[0092] Figure 1 WO3, W provided in Example 1, Example 2 and Example 3 18 O 49 and WO3-W 18 O 49 TEM image of composite photothermal catalytic material; Figure 1 a) It can be seen that WO3 nanorods were successfully prepared, and each nanorod has a uniform size without forming flakes; Figure 1 b) The size of the nanorods can be more clearly seen, which are rod-shaped objects with a radius of about 50nm. 18 O 49 Nanoclusters are obviously different. Since they are structures formed by the self-growth of a large number of nanowires, the clusters appear to be more disordered. Figure 1 c) It can be seen that W 18 O 49 Nanoclusters are distributed in a spherical shape, and one cluster is composed of a large number of nanowires, with a very large specific surface area. Figure 1 df) are different proportions of WO3-W 18 O 49 TEM images of composite materials, from left to right: WO3-W 18 O 49 -30, WO3-W 18 O 49 -150, WO3-W 18 O 49 -300; It is not difficult to see from the figure that due to the small amount of WCl6 added during the solvothermal process, such as Figure 1 As shown in d), although the nanowires are successfully loaded on the WO3 nanorods, the loading amount is small; if the amount of WCl6 added is too much, such as Figure 1 f), the nanowires become short and thin rods instead of nanowires; if the loading amount is appropriate, such as Figure 1 As shown in e), the nanowires are uniformly loaded on the WO3 nanorods in a wrapped shape, making the surface rough and greatly increasing the specific surface area.
[0093] Figure 2 WO3, W provided in Example 1, Example 2 and Example 3 18 O 49 and WO3-W 18 O 49 HRTEM and EDS images of composite photothermal catalytic materials; Figure 2 In (a), we can observe that W 18 O 49 Nanowires grown on WO3 nanorods, illustrating the composite structure. Figure 2 (b) shows a magnified image of the WO3 nanorod region, revealing two sets of lattice fringes at 0.25 nm and 0.38 nm, corresponding to the (001) crystal plane and W 18 O 49 The (010) crystal plane of the nanowires confirms the successful formation of a composite with high crystallinity. Figure 2 (c)-(f) show the uniform distribution of W and O elements on the nanorods and their surfaces, further proving that WO3-W 18 O 49 Successful integration of composite materials.
[0094] Figure 3 WO3, W provided in Example 1, Example 2 and Example 3 18 O 49 and WO3-W 18 O 49 Infrared absorption spectrum of composite photothermal catalytic material; the black line in the figure shows the Fourier transform infrared spectrum of pure WO3 nanorods. It can be seen that at a wave number of 818cm-1 There is a strong characteristic peak at the position of , which is caused by the vibration of the WOW bond in the WO3 nanorods; the red line in the figure shows the Fourier transform infrared spectrum of pure W18O49 nanoclusters. It can be seen that at the wave number of 658cm -1 and 595cm -1 There are two obvious characteristic peaks at the position of W. 18 O 49 The other spectral lines in the figure represent the stretching vibration of WO3-W 18 O 49 -30, WO3-W 18 O 49 -150 and WO3-W 18 O 49 The Fourier transform infrared spectra of the -300 nanocomposites clearly show that the three nanocomposites have -1 There are characteristic peaks at the positions due to the vibration of WOW bonds in WO3 nanorods, and the intensity is consistent. 18 O 49 The characteristic peak caused by the stretching vibration of W=O and OWO bonds in the nanoclusters is WO3-W 18 O 49 -150 is the most obvious, which is consistent with what the TEM image shows.
[0095] Figure 4 WO3, W provided in Example 1, Example 2 and Example 3 18 O 49 and WO3-W 18 O 49 XRD spectrum of composite photothermal catalytic material; compared with WO3-W 18 O 49 It is not difficult to find that in addition to the diffraction peaks of the (100) and (200) crystal planes of the WO3 nanorods, there is also an obvious diffraction peak at a 2θ angle of 23.478°, which is obviously the W 18 O 49 At the same time, as the amount of WCl6 added in the solvothermal step increases, W 18 O 49 The diffraction peak of the cluster (010) crystal plane is becoming more and more obvious, which is also related to Figure 1 The TEM image of WO3-W 18 O 49 Successful compounding of nanocomposites.
[0096] Figure 5 WO3, W provided in Example 1, Example 2 and Example 3 18 O 49 and WO3-W 18 O 49 UV-visible absorption spectra and Tauc plots of composite photothermal catalytic materials; UV-visible absorption spectra of all prepared samples are shown in Figure 5 a). For WO3 nanorods (black line), the cutoff wavelength for light absorption is around 440nm. It can be seen that WO3 nanorods have strong absorption of ultraviolet and some visible light (wavelength < 440nm), but the absorption of visible light after 440nm is weak and narrow. It is worth noting that WO3 nanorods (WO3 NRs) show obvious absorption tails when the wavelength is greater than 500nm, which is attributed to the presence of W on the surface of WO3 nanorods. 5+ and oxygen vacancies. For W 18 O 49 As for the nanoclusters (red line), due to the rich oxygen vacancies in them, obvious absorption can be seen in the visible light region, and even the visible light absorption in the band after 700nm is stronger than that in the ultraviolet region, which just makes up for the insufficient visible light absorption of WO3 nanorods themselves and can better utilize light energy. 18 O 49 A series of nanocomposites with pure WO3 nanorods, W 18 O 49 It is not difficult to see that WO3-W nanoclusters 18 O 49 The light absorption capacity of the series of nanocomposites basically inherits the light absorption capacity of pure WO3 nanorods and W 18 O 49 Advantages of nanoclusters, at the same time in WO3-W 18 O 49 -300 nanocomposites also have ultraviolet and visible light absorption capabilities that exceed those of pure WO3 nanorods and W 18 O 49 In addition, WO3-W 18 O 49 The ultraviolet absorption spectra of the series of composite materials all showed an obvious red shift, so their band gaps became narrower. Figure 5 b) WO3 nanorods, W 18 O 49 Nanoclusters and WO3-W 18 O 49The Tauc plot of the nanocomposite material clearly shows the band gap of the prepared material. α, ν, A and Eg are the absorption coefficient, optical frequency, proportional constant and band gap respectively. 18 O 49 Nanoclusters and WO3-W 18 O 49 The Eg values of the nanocomposites are 3.34, 2.95, and 2.89 eV, respectively. 18 O 49 The band gap of the nanocomposite material is the narrowest, indicating a strong absorption capacity in the visible light region and improved luminescence efficiency.
[0097] Figure 6 WO3, W provided for Application Example 1, Application Example 2, Application Example 3, Comparative Application Example 1, and Comparative Application Example 2 18 O 49 and WO3-W 18 O 49 Performance comparison of photothermal catalytic cyclohexane oxidation of composite photothermal catalytic materials; Figure 6 a) It can be seen that WO3 nanorods (WO3 NRs) have industrial-grade photothermal synergistic catalytic performance, with a conversion rate of 4.72% and a selectivity of 97.78%. 18 O 49 Due to the better spectral absorption ability and rough surface of nanoclusters, the conversion rate of photothermal catalytic selective oxidation of cyclohexane reached 6.52% and the selectivity reached 98.52%. Figure 6 b) It can be seen that the conversion rates of all catalysts are basically around 97-99%. Therefore, the intensity of the photothermal synergistic catalytic activity of all catalysts is as follows: WO3-W 18 O 49 -150>WO3-W 18 O 49 -30>WO3-W 18 O 49 -300>W 18 O 49 Under the same conditions (reaction temperature of 120°C, reaction time of 8h, irradiation with a 300W xenon lamp), it was found that the catalyst with the best photothermal catalytic performance was WO3-W 18 O 49 -150 nanocomposite materials. After that, comparative experiments with different reaction times were conducted to explore the effects of different reaction temperatures on the photothermal synergistic catalytic selective oxidation of cyclohexane. The results are as follows Figure 6 c). It is not difficult to see that WO3-W 18 O 49-150 nanocomposite material is exposed to 300W Xe lamp at 120℃. As time goes by, the conversion rate of cyclohexane oxidation to KA oil will increase. However, the conversion rate from 8 hours to 10 hours is only 0.32%, which is not worthwhile from the perspective of energy consumption and green environmental protection. 18 O 49 -150 nanocomposite material has the best reaction time of 8 hours. 18 O 49 -150 nanocomposite material was used as the catalyst, the performance of different catalytic methods for the selective oxidation of cyclohexane was also compared. Figure 6 It can be clearly seen that the conversion rate of cyclohexane selective oxidation by photothermal catalysis is greater than that by photocatalysis and thermal catalysis, which fully demonstrates the superiority of photothermal catalysis. Figure 6 e) Indicates that WO3-W is also used 18 O 49 -150 nanocomposite material as a catalyst, the performance comparison of photothermal catalytic selective oxidation of cyclohexane and thermal catalytic selective oxidation of cyclohexane at different temperatures. It can be seen that no matter at which temperature, the catalytic efficiency of photothermal catalysis is always much higher than that of thermal catalysis. In addition, the catalytic efficiency of photothermal catalysis at 100°C is higher than that of thermal catalysis at 120°C, which shows that photothermal catalysis does have the effect of lowering the reaction temperature, making the reaction conditions of cyclohexane oxidation no longer so harsh, and has a very large industrial prospect. In order to verify the WO3-W 18 O 49 The catalytic stability of the -150 composite material was tested by continuous photothermal catalytic cyclohexane oxidation for 5 cycles. Figure 6 f), after the second repeated experiment, the conversion rate of the catalyst decreased by 0.47% to 7.99%. The conversion rate of the subsequent repeated experiments was basically maintained at around 8%. It is speculated that after the photothermal synergistic catalytic selective oxidation of cyclohexane, WO3-W 18 O 49 -150 nanocomposites are quenched. But in general, WO3-W 18 O 49 The conversion rate and selectivity of the -150 composite material are higher than those of pure WO3 nanorods.
Claims
1. A WO3-W with oxygen vacancy 18 O 49 The method for preparing a composite catalytic material is characterized in that: The following steps are included in sequence: S1. Preparation of WO3 nanorods: Add tungsten source and sodium chloride to ultrapure water, and use hydrochloric acid to adjust the pH of the solution to acidic, and perform hydrothermal reaction at 180°C for 20-24h. The reaction product is eluted and dried to obtain WO3 nanorods. The molar ratio of sodium tungstate dihydrate to sodium chloride is 1:1.5-1:2; S2. Preparation of WO3-W 18 O 49 Tungsten hexachloride is added to anhydrous ethanol, and then the solution is transferred to WO3 nanorods and dispersed evenly by ultrasonication, and a hydrothermal reaction is carried out at 150-170°C for 12-36 hours. The reaction product is eluted and dried to obtain WO3-W 18 O 49 : The molar ratio of the tungsten hexachloride to the WO3 nanorods is 1:3-1:
30.
2. The oxygen-rich vacancy WO3-W according to claim 1 18 O 49 The method for preparing a composite catalytic material is characterized in that: The tungsten source described in S1 is sodium tungstate dihydrate.
3. The oxygen-rich vacancy WO3-W according to claim 1 18 O 49 The method for preparing a composite catalytic material is characterized in that: The pH of S1 is 2.
4. The oxygen-rich vacancy WO3-W according to claim 1 18 O 49 The method for preparing a composite catalytic material is characterized in that: The tungsten source described in S2 is tungsten hexachloride.
5. The oxygen-rich vacancy WO3-W according to claim 1 18 O 49 The method for preparing a composite catalytic material is characterized in that: The washing in step 1) is first performed with water and then with anhydrous ethanol.
6. The oxygen-vacancy-rich WO3-W according to claim 1 18 O 49 The method for preparing a composite catalytic material is characterized in that: The washing in step 2) is first performed with water and then with anhydrous ethanol.
7. An oxygen-vacancy-rich WO3-W 18 O 49 The composite catalytic material is characterized in that The method is prepared by any one of claims 1 to 6.
8. The oxygen-rich vacancy WO3-W according to claim 7 18 O 49 The composite catalytic material is used for photothermal catalytic cyclohexane oxidation reaction.
9. A method for photothermal catalytic cyclohexane oxidation reaction, characterized in that: The steps are as follows: 1) Weigh the WO3-W described in claim 7 18 O 49 -150 composite photothermal catalytic material is dissolved in cyclohexane and acetone; 2) pouring the solution prepared in step 1) into a photothermal reactor, sealing the reactor, and filling it with dry air at 1.0-2.0 MPa; 3) React at 100-150°C under xenon lamp irradiation for 6-10 hours; 4) After the reaction is completed, wait for the reactor to cool to room temperature and measure the conversion rate and selectivity; The WO3-W 18 O 49 The ratio of -150 composite photothermal catalytic material to cyclohexane is 20 mg:10 mL.
10. The method for photothermal catalytic cyclohexane oxidation reaction according to claim, characterized in that: The volume ratio of cyclohexane to acetone is 2:1.